Projeto e análise de controladores a partir da identificação em malha fechada: estudo de casos - Alessandra Rose Crosara Rios (2007)
In this work, the performance of some closed loop systems are compared for different controllers tunning and design. The studies are implemented in a pilot scale plant, called Interactive Tanks System, available at LCPI. Researches for the level control loop are accomplished, and by that, the system, originally MIMO (Multiple Inputs Multiple Outputs), is approached as SISO (Single Input Single Output). The flow control loop of the tanks is forced to operate on open loop, with a constant opening of the valve. The design of the controllers is implemented from mathematic models, which are obtained from some identification procedure. For that, identification methods for closed and open loop are studied, as their important proprieties. The controllers designed are those called two degree of freedom, specifically the RST, and the technic used is the Pole Placement, whose reference model have some proprieties, like the maximum overshoot, settling time and rise time permitted to the system. All the approach in the work is made with discret models of the system, taking easier the implementation of the controllers on software of LCPI. Some results for simulated systems are also presented, to a better understanding and application of the identification and design technics.